P055: Quality assessment and improvement evaluation of return visits to the emergency department for ultrasound. (May 2019) - Giffin, D.; Van Aarsen, K.; Brine, M.; Church, K.; Fotheringham, M.; Pillon, S.; Poss, C.; Price, L.; Dukelow, A.; Dreyer, J.
Abstract : Introduction : Depending on the time and day of initial Emergency Department (ED) presentation, some patients may require a return to the ED the following day for ultrasound examination. Return visits for ultrasound may be time and resource intensive for both patients and the ED. Qualitative experience suggests that a percentage of return ultrasounds could be performed at a non-ED facility. Our objective was to undertake a retrospective audit of return for ultrasound usage, patterns and outcomes at 2 academic EDs.Methods : A retrospective review of all adult patients returning to the ED for ultrasound at both LHSC ED sites in 2016 was undertaken. Each chart was independently reviewed by two emergency medicine consultants. Charts were assessed for day and time of initial presentation and return, type of ultrasound ordered, and length of ED stay on initial presentation and return visit. Opinion based questions were considered by reviewers, including urgency of diagnosis clarification required, if symptoms were still present on return, and if any medical or surgical treatment or follow up was arranged based on ultrasound results. Agreement between reviewers was assessed.Results : After eliminating charts for which the return visit was not for a scheduled ultrasound examination, 328 patient charts were reviewed. 63% of patients were female and median [IQR] age was 40 years [27-56]. Abdomen/pelvis represented 50% of the ultrasounds; renal 24%; venous Doppler 15.9%. Symptoms were still present and documented in 79% of cases. 22% of cases required a medical intervention and 9% an immediate surgical intervention. 11% of patients were admitted to hospital on their return visit. Outpatient follow-up based on US results was initiated in 29% of cases. Median [IQR] combined LOS was 479.5 minutes [358.5-621.75]. Agreement between reviewers for opinion based questions was poor (63%-96%).Conclusion : Ideally, formal ultrasound should be available on a 24 hour basis for ED patients in order to avoid return visits. A percentage of return for ultrasound examinations do not result in any significant change in treatment. Emergency departments should consider the development of pathways to avoid return visits for follow up ultrasound when possible. The low incidence of surgical treatment in those returning for US suggests that this population could be served in a non-hospital setting. Further research is required to support this conclusion.